Genome skimming supports two new crayfish species from the genus Pacifastacus Bott, 1950 (Decapoda: Astacidae) - Larson, Eric R.; Abbott, Cathryn L.; Gilmore, Scott R.; Helbing, Caren C.; Lopez, Mark Louie D.; Macintosh, Hugh; Stenhouse, Liane M.; Williams, Bronwyn W.; Usio, Nisikawa (Zootaxa, 2025)
Recent phylogenetic analyses have suggested that the Signal Crayfish, Pacifastacus leniusculus (Dana, 1852), contains two highly distinct lineages that merit recognition as species. We further investigate these lineages here using genome skimming to conduct phylogenetic analyses on mitogenomes and highly repetitive 18S, 28S, and H3 nuclear markers. We also analyze morphological characters of these putative species to identify traits that may facilitate their identification in the field. Phylogenetic trees of mitogenomes support these lineages as species in the family Astacidae, and phylogenetic trees based on concatenated nuclear markers return comparable topologies. We describe these crayfishes as the Misfortunate Crayfish, Pacifastacus malheurensis sp. nov., which occurs in central and eastern Oregon, United States, and the Okanagan Crayfish, Pacifastacus okanaganensis sp. nov., which occurs in south central British Columbia, Canada and north central Washington, United States. Both of these species of Pacifastacus face conservation risks from displacement by non-native invasive crayfishes, but P. malheurensis sp. nov. is especially vulnerable to the rapidly spreading Rusty Crayfish, Faxonius rusticus (Girard, 1852), in central Oregon.